Coordination of Actors, Farmers - Processors and the Social Welfare of the Citizens in Peja - Kolica, Sylë (European Journal of Economics and Business Studies, 2016)
Kosovo society is considered as strong consumer society with the need for liberalization of the labor market, active participation in the process of globalization and the promotion of "knowledge economy". Coordination of actors through associations and other forms of temporary association are prerequisite for enterprises, especially agribusiness related strategies growth and sustainability and being pro-business constitutes an essential condition to be pro-social, aware of the necessity of reconciliation policies free social market. Social Responsibility of enterprises, especially agribusiness Peja defined as a strong consumer, labor market liberalization and active participation of these enterprises with coordination of stakeholders in the process of globalization and the promotion of "knowledge economy". Peja agribusiness enterprises nowadays qualified as a period of liberalization are the first steps to understanding their fair economy intends putting it at the service of people considering the effectiveness of the market and minimal state. So in this case the state local government should create enabling environment for free breathing of these companies which are the only option for the social welfare of the citizens of the municipality of Peja and poverty reduction. The organization and coordination of stakeholders, farmers - among others profit maker also has another important instrument is therefore an instrument of social development under (JMKEYNES) Laissez faire works in these enterprises on the basis of the law of supply and demand, which itself regulates economic life of the citizens of Pec. Specification and focus on specific language variables gives discussed and explained the problem. Search theoretical judged and evaluated as the product of a cultural and institutional dispute.